2014
DOI: 10.1007/s11010-014-2234-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-433 inhibits cell proliferation in hepatocellular carcinoma by targeting p21 activated kinase (PAK4)

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. P21-activated kinase 4 (PAK4) has been identified as an oncogenic protein in a variety of cancers. However, the contribution and regulation of PAK4 in HCC remain poorly understood. In the present study, we found that inhibition of PAK4 expression by specific shRNA significantly attenuated HCC cell proliferation. Moreover, we show that microRNA-433 (miRNA-433) could directly target PAK4 through the miRNA-433 binding sequence at the 3'-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Decreased miR-433 expression levels are correlated with distant metastasis and pathological TNM stage in patients with gastric cancer (21). MiR-433 downregulation has also been reported in colorectal cancer (22), hepatocellular carcinoma (23,24), myeloproliferative neoplasms (34), oral squamous cell carcinoma (35), ovarian cancer (36), retinoblastoma (37) and glioma (38). Conversely, miR-433 is overexpressed in osteosarcoma (39).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Decreased miR-433 expression levels are correlated with distant metastasis and pathological TNM stage in patients with gastric cancer (21). MiR-433 downregulation has also been reported in colorectal cancer (22), hepatocellular carcinoma (23,24), myeloproliferative neoplasms (34), oral squamous cell carcinoma (35), ovarian cancer (36), retinoblastoma (37) and glioma (38). Conversely, miR-433 is overexpressed in osteosarcoma (39).…”
Section: Discussionmentioning
confidence: 95%
“…The findings of the present study suggested that miR-433 may be considered as a potential therapeutic target for the treatment of NSCLC. MiR-433 dysregulation is involved in numerous types of human cancer (21)(22)(23). For example, miR-433 is downregulated within gastric cancer tissues and cell lines (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAK4 modulation of CRAF and BAD phosphorylation inhibits apoptosis in endothelial cells (Alavi et al, 2003). The biology of PAK4 overexpressing cancer cells has also been shown to be regulated by PAK4 targeting by miR-199a/b-3p (Hou et al, 2011), miR-433 (Xue et al, 2015), and miR-224 (Li et al, 2014) in hepatocellular carcinoma cells. PAK4 also phosphorylates Smad2 on Ser465 in growth factor-stimulated cancer cells (Wang et al, 2014).…”
Section: Pak1 and Pak4 In Cancer Progressionmentioning
confidence: 99%
“…Recent studies have shown that miR-433-3p, a tumor suppressor located on chromosome 12, inhibited the proliferation, invasion, and drug resistance of various tumor cells, and repressed the growth of hepatocellular carcinoma cells [5, 6]. Yang et al that miR-433-3p blocked the invasion of liver cancer cells [7].…”
Section: Introductionmentioning
confidence: 99%